An Experimental Study Of A Solar Water Heater Of Prismatic Right Triangular Cross-Section Area - Rahman M. Homadi, Abdul; T. Ahmed, sabah (Anbar Journal of Engineering Sciences, 2011)
An experimental study was done on a solar water heater which consists of two prisms of orthogonal triangle cross-section with a 210 liters capacity . The heater was easy to make and has a low cost when comparted with other types of solar water heaters that it usually the collector separate on the water store. The study included experimental investigations , the experimental investigation was done under the Iraqi environmental conditions at Baghdad for the period in summer and winter seasons in 2006 but the calculation for only two days 15/7/2006 and 6/12/2006 . The study included testing the heater with & without loading and it tested in 13/12/2006and14/12/2006. draining hot water from storage tank at different rates . The experimental result show the ability to get hot water at 46oC at December i.e. a temperature rise at 30oC with 16oC initial temperature .